Klasifikasi Kelayakan Data Beasiswa PIP Pada MINU Sumokali Menggunakan Metode Decision Tree - Rofiq, M. Ainun; Kurniati, Neny; Editya, Arda Surya (JATISI, 2024)
Every new academic year Madrasah Ibtida'iyah Nahdlatul Ulama Sumokali Candi Sidoarjo collects data on prospective PIP scholarship recipients, this is done by looking at the files that have been collected by students from the school. In selecting prospective PIP scholarship recipients at Madrasah Ibtida'iyah Nahdlatul Ulama Sumokali Candi Sidoarjo who will be submitted, they still experience difficulties in making or determining decisions due to the large number of students who register and because the selection process still uses a manual system, it takes a very long time and is less effective for the parties. administration, with these problems in mind, the author conducted research on how to apply data mining using the Decision Tree method and how to determine the accuracy of the results using the C4.5 algorithm to determine whether students who are potential PIP scholarship recipients are eligible or not. The amount of PIP scholarship classification data collected was 240 data from last year's data, so we implemented this data into the website system to form an application that can predict the eligibility of PIP scholarship recipients. Based on testing the level of accuracy with system calculations, the accuracy results were 83.33%.